1989
DOI: 10.1097/00001888-198906000-00001
|View full text |Cite
|
Sign up to set email alerts
|

The New Mexico experiment

Abstract: Over the past ten years the University of New Mexico School of Medicine has conducted an educational experiment featuring learner-centered, problem-based, community-oriented learning. The experiment was introduced into an established institution by means of an innovative educational track running parallel to the more conventional curriculum. Students in the innovative track, compared with those in the conventional tract, tended to score lower on the National Board of Medical Examiners (NBME) Part I examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(8 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Advantages and disadvantages of PBL have been stated elsewhere (Barrows and Tamblyn, 1980;Kaufman et al, 1989) and we have listed the positive and negative aspects of our program as viewed by students and faculty. Since we did not employ the PBL sessions as tools to learn academic subjects, we are not able to comment on using this approach exclusively to teach didactic material.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Advantages and disadvantages of PBL have been stated elsewhere (Barrows and Tamblyn, 1980;Kaufman et al, 1989) and we have listed the positive and negative aspects of our program as viewed by students and faculty. Since we did not employ the PBL sessions as tools to learn academic subjects, we are not able to comment on using this approach exclusively to teach didactic material.…”
Section: Discussionmentioning
confidence: 86%
“…Incorporated in this process is gathering information from pertinent sources (experts in the field, books, journals, etc. ), analyzing the information, developing hypotheses, and then sharing labors and thoughts with colleagues (Kaufman et al, 1989). Information gained in PBL is important and most likely will be retained longer by the student because he or she has been active in producing the information.…”
Section: Introductionmentioning
confidence: 99%
“…The approach occupies a middle ground between shorter‐term training opportunities in rural and remote settings with no distributed campus (e.g. the Parallel Rural Community Curriculum at Flinders University in South Australia 12 and the Practical Immersion initiative offered by the University of New Mexico 13 ), and stand‐alone medical schools in traditionally under‐serviced settings, such as Keele University’s Medical School in northern England (formerly a distributed campus of Manchester University’s Medical School) 14 and the Northern Ontario School of Medicine 15 …”
Section: Introductionmentioning
confidence: 99%
“…The mean number of participants was 2047 (38–14,370). There was a propensity towards surveying already practising physicians (n = 22,002), although Kaufman et al [14] used final year medical students (n = 511). Matsui et al [9] looked at a cohort of female medical school graduates who had graduated from Tokyo Women’s Medical University over a series of years (1989–2003).…”
Section: Resultsmentioning
confidence: 99%
“…Kaufman et al [14] looked at self-reported student interest in specific specialities and how this changes throughout medical school with a PBL/Non-PBL curriculum. They found that significantly more PBL students retained an interest in a career in primary care (P = 0.05) and significantly more PBL students switched to an interest in primary care during medical school (P = 0.05).…”
Section: Resultsmentioning
confidence: 99%